William Woodward : American Impressionist - Hinckley, Robert C. (Book collections on Project MUSE., 2009)
"William Woodward was a powerful force in New Orleans and the art world. His legacy endures. This book is a compilation of his work, spanning his career as an artist. The authors of the essays in this book -- all well known and respected in their fields -- offer their own unique perspectives on Woodward, his life, his influence, and his art" -- inside cover.